PEMUTAKHIRAN DATA PEMILIH PADA PEMILIHAN BUPATI DAN WAKIL BUPATI KABUPATEN BENGKALIS DI KECAMATAN MANDAU DAN KECAMATAN BANTAN TAHUN 2015 - Rahmad Nuryadi Putra; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study entitled "Voter Data Updates On Election of Regent and Vice Regent of Bengkalis in the District Mandau and District Bantan Bantan 2015". Problems found in this study were the organizers have difficulties in verifying factual.The research questions that the authors give in this study is "What is the process of updating the data of voters and the factors that influence the results of updating the data?" The aim of this study to analyze the process of updating the data and to know the factors that affect the results of updating the data. The method used in this study is a qualitative approach which explains descriptive data. Data collection techniques used were interviews and documentation. While the source of the data used primary data as well as some secondary data.Based on the results of research conducted there are some findings: First, the management information system of voter data due to negligence online systems officer; Second, negligence Officer Update Data Selector. This is due to the inaccuracy of the officer while doing verfiikasi factual; Third, recording a result of reallocation of village population and population movements; Fourth, public participation such as the people are not active in the process of updating the data; Fifth, the conditions of Potential Voters List Electoral caused delays in completion of recording of e-ID card; and Sixth, conditions caused Population Identification Number of recorded names does not meet the standards diprogramkan.proses updating and management of data has not been able to be performed optimally.Keyword: Data Update Voters, Public Pemihan Commission, the Permanent Voter List